Measurement of Refractive Index and Thickness of Multi Layer Systems Using Fourier Domain Optical Coherence Tomography - Rajai, Payman (Université d'Ottawa / University of Ottawa, 2016)
A multilayered system is a good model for many optical systems. An optical coherence tomography (OCT) system can provide fundamental information about the refractive index distribution of the sample and enables images to be corrected for geometric accuracy, but this requires the separation of refractive index and physical thickness for each layer from the measured optical paths. In this thesis a novel approach for simultaneous extraction of index and thickness of multi layer systems and the last medium index of refraction in a single experiment using only the object’s spectral response available by any Fourier Domain OCT system without using any additional outside measurements is introduced. The method is based on a novel matrix equation that uses the reflected spectrum from the object and the measured optical thickness. In the presence of slight error of measuring optical thickness, the parameters extraction has wavenumber dependency. A novel method is used to select the suitable set of spectral components that reduces the extracted parameters error. The parameters extraction method is followed by a fitting process for optimized results. The method works the best for low contrast index distribution even in the presence of relatively large optical thickness measurement error.
Keywords: Optical Coherence Tomography; Fourier Domain; Refractive Index; Multi Layer System; Spectral Analysis